Linking the Warburg effect to endometrial receptivity: metabolic parallels in embryo implantation - Zhang, Xiaoyang; Zhu, Qingwen; Nie, Weiduo; Yan, Xiaoxue; Yuan, Zhihua; Tian, Leiyu (Frontiers in Cell and Developmental Biology, 2025)
IntroductionEndometrial receptivity (ER), critical for successful embryo implantation and a major limiting factor in infertility affecting ∼1 in 6 couples globally, remains poorly understood, with few effective interventions targeting the embryo-endometrium interaction. Intriguingly, similarities exist between the implantation microenvironment and the Warburg effect, a metabolic hallmark of cancer characterized by aerobic glycolysis, lactate production, and low pH.MethodsWe conducted a comprehensive review (PubMed search up to April 2025) using keywords related to the Warburg effect (aerobic glycolysis, lactate, mitophagy), infertility (IVF, embryo implantation, TCM), cancer, cytokines (IL-1, LIF, TGF-β), and hormones (estrogen, progesterone).ResultsThe review identified significant mechanistic parallels: 1) Blastocysts and trophoblasts establish a pro-receptive, high-lactate/low-pH microenvironment via Warburg-like glycolysis; 2) Shared immune modulation occurs (e.g., PI3K-AKT-FOXO1 pathway), balancing inflammatory attachment and immune tolerance; 3) Glycolysis regulates key ER-associated genes (e.g., MRAP2, BCL2L15) and cytokines (IL-1, LIF, TGF-β); 4) Invasive trophoblast behavior mirrors cancer cell invasion, potentially fueled by Warburg metabolism; 5) Hormones (estrogen, progesterone) critically orchestrate glycolytic enzyme expression (e.g., GLUT1, PFKFB3), substrate availability, and lactate-mediated immune suppression to establish this metabolic state.DiscussionWhile direct experimental evidence linking the Warburg effect to ER is currently limited, the compelling mechanistic overlap offers a novel paradigm for understanding implantation failure. Targeting this shared metabolic-immune-hormonal axis holds immense potential for developing innovative strategies (e.g., metabolic modulators, refined TCM approaches) to improve ER, enhance embryo implantation rates in infertility (including IVF) and recurrent miscarriage, ultimately advancing global reproductive health. Further research is needed to validate core mechanisms.